2020
DOI: 10.3389/fimmu.2020.01156
|View full text |Cite
|
Sign up to set email alerts
|

B Lymphocytes as Targets of the Immunomodulatory Properties of Human Amniotic Mesenchymal Stromal Cells

Abstract: Mesenchymal stromal cells (MSC) from the amniotic membrane of human term placenta (hAMSC), and the conditioned medium generated from their culture (CM-hAMSC) offer significant tools for their use in regenerative medicine mainly due to their immunomodulatory properties. Interestingly, hAMSC and their CM have been successfully exploited in preclinical disease models of inflammatory and autoimmune diseases where depletion or modulation of B cells have been indicated as an effective treatment, such as inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 80 publications
2
32
0
Order By: Relevance
“…In keeping with the known immunomodulation of P‐MSCs toward T cells, NKs, and myeloid cells, our findings here further extend those immunomodulatory properties toward peripheral B cells, with significant induction of multiple populations of IL‐10‐producing Bregs compared to BM‐MSCs. Indeed, an increasing number of studies show that fetal‐source umbilical cord‐MSCs suppress in vitro B‐cell proliferation and halt terminal differentiation 55,56 ; two very recent reports using amniotic membrane‐MSCs demonstrate similar findings, 57 and decreased pulmonary B‐cell recruitment and maturation was found in an in vivo lung injury model 58 . Moreover, our lab and others have found that fetal‐source MSCs 29,59 —in contrast to adult BM‐MSCs 60 —may not require inflammatory priming for immunomodulation, an aspect that has not been evaluated for MSC interactions with B cells.…”
Section: Discussionmentioning
confidence: 96%
“…In keeping with the known immunomodulation of P‐MSCs toward T cells, NKs, and myeloid cells, our findings here further extend those immunomodulatory properties toward peripheral B cells, with significant induction of multiple populations of IL‐10‐producing Bregs compared to BM‐MSCs. Indeed, an increasing number of studies show that fetal‐source umbilical cord‐MSCs suppress in vitro B‐cell proliferation and halt terminal differentiation 55,56 ; two very recent reports using amniotic membrane‐MSCs demonstrate similar findings, 57 and decreased pulmonary B‐cell recruitment and maturation was found in an in vivo lung injury model 58 . Moreover, our lab and others have found that fetal‐source MSCs 29,59 —in contrast to adult BM‐MSCs 60 —may not require inflammatory priming for immunomodulation, an aspect that has not been evaluated for MSC interactions with B cells.…”
Section: Discussionmentioning
confidence: 96%
“…Further analyses have shown that MSCs also markedly inhibit the pDC-induced maturation of B cells. Similarly, Magatti et al (2020) reported a decreased proliferation, maturation, and antibody secretion mediated by MSCs. They also demonstrated that the conditioned medium of MSCs reduces the expression of CD205, CD14, and Toll-like receptor 9 by B cells and that the observed effects are partially mediated by PGE2.…”
Section: Regulation Of Adaptive Immunity By Mscsmentioning
confidence: 94%
“…Given these premises, strategies affecting B cells and their activation status may represent a valid therapeutic approach in PE. Perinatal derivatives constitute a promising tool in this context, especially in the light of the recent identification of B cells as a target of their immune modulatory action [ 85 , 86 ]. The next paragraphs outline the state of the art of the crosstalk between perinatal derivatives and B cells and the potential for this interaction to be translated into a valid therapeutic option for PE.…”
Section: Focus On B Cellsmentioning
confidence: 99%